1999
DOI: 10.1007/s004210050520
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-induced hypoxaemia in highly trained cyclists at 40% peak oxygen uptake

Abstract: A group of 15 competitive male cyclists [mean peak oxygen uptake, VO2peak 68.5 (SEM 1.5 ml x kg(-1) x min(-1))] exercised on a cycle ergometer in a protocol which began at an intensity of 150 W and was increased by 25 W every 2 min until the subject was exhausted. Blood samples were taken from the radial artery at the end of each exercise intensity to determine the partial pressures of blood gases and oxyhaemoglobin saturation (SaO2), with all values corrected for rectal temperature. The SaO2 was also monitore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
40
1
5

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 30 publications
(70 reference statements)
5
40
1
5
Order By: Relevance
“…In the H group, SaO 2 was lower than in the NH group from 25% up to 100% of maximal power and was significantly decreased from resting values from 75%, which is in agreement with previous studies in adults (26,27). Indeed, Rice et (27) reported significantly higher values of alveolar to arterial difference in oxygen pressure from 30% V O 2max in subjects who exhibited gas exchange disturbance than in control subjects.…”
Section: · Kgsupporting
confidence: 90%
See 2 more Smart Citations
“…In the H group, SaO 2 was lower than in the NH group from 25% up to 100% of maximal power and was significantly decreased from resting values from 75%, which is in agreement with previous studies in adults (26,27). Indeed, Rice et (27) reported significantly higher values of alveolar to arterial difference in oxygen pressure from 30% V O 2max in subjects who exhibited gas exchange disturbance than in control subjects.…”
Section: · Kgsupporting
confidence: 90%
“…A major mechanism in EIAH in adults is a ventilatory limitation during exercise, termed relative hypoventilation (5,7). In adults, the submaximal decrease in SaO 2 seems explained by a relative hypoventilation associated with a V A/Q c mismatch (26,27) V A/Q c mismatch was not measured in the present study; however, we found lower values of ⌬V E /⌬V CO 2 during submaximal exercise in hypoxemic children (Fig. 2).…”
Section: · Kgcontrasting
confidence: 51%
See 1 more Smart Citation
“…This participant also experienced marked increases in PCO 2 (sometimes reaching 60 mm Hg), indicative of inadequate hyperventilation. Indeed, desaturation during submaximal (40% 2 O V  max) exercise has been reported previously in trained cyclists and is attributed to an inadequate hyperventilatory response (Rice et al 1999). …”
Section: Ventilatory Responsesmentioning
confidence: 63%
“…Studies examining EIAH have primarily focused on aerobic trained individuals [4,8,[12][13][14][15][16][17][18]. Interestingly, no studies have examined the EIAH in anaerobic trained athletes.…”
mentioning
confidence: 99%